Factors affecting paddy farm income in East Kalimantan, Indonesia - KARMINI KARMINI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Karmini.2017. Factors affecting paddy farm income in East Kalimantan, Indonesia. Biodiversitas 18: 101-108. The development of paddy farming in East Kalimantan Province faces problem and challenge as the low level of paddy farm income. Consequently, efforts are needed to increase paddy farm income. The objective of this study is to determine factors affecting paddy farm income. This study was carried out in East Kalimantan Province, Indonesia (Now, the province was divided into two, East Kalimantan and North Kalimantan). The two-stage cluster sampling was applied to select one cities and three Districts (Bontang City, Kutai Kartanegara District, and Penajam Paser Utara District) and to choose 3 sub-cities and 6 sub-districts (Sub-cities of South Bontang, North Bontang, and West Bontang and Sub-districts of Tenggarong Seberang, Loa Janan, Muara Muntai, Babulu, Penajam, and Waru) as the study areas. The simple random sampling was used to choose the households of paddy farmers as respondents. This study assessed 380 paddy households as respondents. The regression function was used to analyze the data. The result of F test shows age of household head, depreciation of tools, experience of household head in paddy farming, labour cost, land cultivation cost, paddy farm size, raw materials cost, and rice requirement of the household, collectively, very significantly affect paddy farm income in East Kalimantan Province, Indonesia. The results of t tests show land cultivation cost, paddy farm size, and raw materials cost, individually, significantly affect paddy farm income in East Kalimantan Province, Indonesia. Meanwhile, labour cost, individually, significantly affect paddy farm income. However, the other variables, individually, are not significantly affect paddy farm income. Keywords: East Kalimantan, farm, income, Indonesia, paddy